Prognostic value of endothelial activation and stress index in mechanical thrombectomy for patients with acute ischemic stroke - Zhu, Xiaohua; Lu, Yunnan; Xu, Yaojia; Li, Yongxin; Dai, Qingyong; Chang, Xia (Frontiers in Aging Neuroscience, 2025)
Background and purposeThe Endothelial Activation and Stress Index (EASIX) is a marker of endothelial dysfunction. This study aimed to explore the association between the EASIX score and unfavorable outcome in patients with acute ischemic stroke (AIS) undergoing mechanical thrombectomy (MT) treatment.MethodsWe enrolled AIS patients treated with MT from a multicenter study between June 2021 to September 2024. The EASIX score was calculated as lactate dehydrogenase (LDH) (U / L) × Creatinine (mg / dL) / Platelet Count (10 ∧ 9 / L). The unfavorable outcome was defined as 90-day modified Rankin scale score 3–6. We used multivariable logistic regression models to investigate the association between EASIX score and unfavorable outcome. A restricted cubic spline analysis was conducted to describe the linear relationship between the EASIX score and unfavorable outcome.ResultsA total of 406 patients (258 [63.5%] male and median age: 71 years) were included in this study. 181 (44.6%) patients experienced unfavorable outcome. The logistic regression models demonstrated a robust association between the EASIX score and unfavorable outcome (log2 transformed odds ratio [OR]: 1.41; 95% confidence interval [CI]: 1.19–1.70; P < 0.001; tertile 3 vs. tertile 1 OR: 2.05; 95% CI: 1.14–3.55; P = 0.017). The restricted cubic spline analysis revealed a linearly increasing association between the EASIX score and the risk of unfavorable outcome (P for nonlinearity = 0.802).ConclusionHigher EASIX levels were significantly related to unfavorable outcome in AIS patients treated with MT. EASIX score may serve as a valuable tool for early risk assessment and outcome prediction in AIS patients.